Cyclin D1 is not an essential target of beta-catenin signaling during intestinal tumorigenesis, but it may act as a modifier of disease severity in multiple intestinal neoplasia (Min) mice. - Wilding, J; Straub, J; Bee, J; Churchman, M; Bodmer, W; Dickson, C; Tomlinson, I; Ilyas, M (2002)
Deregulation of beta-catenin activity is an important step in the development of colorectal cancers. One consequence of this is transcriptional activation of cyclin D1, an oncogene known to be overexpressed in colorectal cancers. We tested the hypothesis that cyclin D1 gene activation is important for intestinal tumorigenesis. Multiple intestinal neoplasia mice (a model for human familial adenomatous polyposis) were crossed with cyclin D1 knockout (Ccnd1(-/-)) mice. Despite the absence of cyclin D1, intestinal tumors still developed. However, Ccnd1(-/-) multiple intestinal neoplasia mice developed significantly fewer tumors than Ccnd1(+/-) or Ccnd1(+/+) mice (P = 0.003). We conclude that cyclin D1 is not essential for intestinal tumorigenesis, but it may act as a modifier gene.